2018
DOI: 10.1016/j.newast.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Photometry of some more neglected bright cataclysmic variables and candidates

Abstract: As part of an effort to better characterize bright cataclysmic variables (CVs) and related systems which have received little attention in the past light curves of four systems (V504 Cen, KT Eri, Ret 1 and CTCV 2056-3014) are analyzed. For some of these stars no time resolved photometry has been published previously. While flickering is observed in all systems except Ret 1, it is particularly strong in V504 Cen and CTCV 2056-3014. In the latter star, a previously observed 15.4 m period, leading to its tentativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Optical photometry of J2056 conducted by Bruch (2018) revealed that the averaged magnitude of the system varies by at least 2.4-mag in comparison with measurements of Augusteijn et al (2010), ranging from V ∼ 17.6 to 15.2 mag, and that it displays strong flickering with an amplitude up to 0.8 mag. Bruch (2018) also suggested that the 15.4-min period claimed by Augusteijn et al (2010) is spurious. Finally, Gaia parallax indicates that J2056 is a nearby system, at a distance (d) of 261.6±7.4 pc (Bailer-Jones et al 2018).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Optical photometry of J2056 conducted by Bruch (2018) revealed that the averaged magnitude of the system varies by at least 2.4-mag in comparison with measurements of Augusteijn et al (2010), ranging from V ∼ 17.6 to 15.2 mag, and that it displays strong flickering with an amplitude up to 0.8 mag. Bruch (2018) also suggested that the 15.4-min period claimed by Augusteijn et al (2010) is spurious. Finally, Gaia parallax indicates that J2056 is a nearby system, at a distance (d) of 261.6±7.4 pc (Bailer-Jones et al 2018).…”
Section: Introductionmentioning
confidence: 84%
“…Here we report on its X-ray properties, which suggest J2056 to be an unusual IP. We also revisit the optical observations of Bruch (2018).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…No filters were employed during the observations. Bruch (2018) found that his unfiltered CCD photometry was approximately equivalent to observations in the V band. He used detectors which are more sensitive in the blue than the one used here (KAF 1602E).…”
Section: Observationsmentioning
confidence: 92%
“…Time was transformed into barycentric Julian Date on the Barycentric Dynamical Time (TDB) scale using the online tool provided by Eastman et al (2010). For subsequent data analysis the MIRA software system Bruch (1993) was employed. A journal of observation is given in Table 1.…”
Section: Observationsmentioning
confidence: 99%